Essays in financial literacy & decision making - Weber, Jörg (2015)
Research in consumer financial decision making has received considerable attention in recent years. This thesis contributes to the literature on financial literacy and measuring underlying behavioural characteristics to explain individual choice, as well as the experimental literature on the certainty effect and robustness of experimental results.